Potential of continuous tPA infusion for multiple-organ failure from lipopolysaccharide-induced disseminated intravascular coagulation in rats. Issue 206 (October 2021) - Suga, Yukio; Tashiro, Kiyomichi; Staub, Yukiko; Komura, Shiori; Yamada, Shinya; Morishita, Eriko; Asakura, Hidesaku
Highlights: tPA could show the improvement effect on organ failure. Thrombocytopenia in DIC was suppressed by tPA administration. Renal dysfunction was lower in the LPS + tPA group than in the LPS group.